2013
DOI: 10.1049/iet-rpg.2012.0234
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and testing of a 250 kW medium‐speed brushless doubly‐fed induction generator

Abstract: This study presents the performance analysis and testing of a 250 kW medium-speed brushless doubly-fed induction generator (DFIG), and its associated power electronics and control systems. The experimental tests confirm the design, and show the system's steady-state and dynamic performance and grid low-voltage ride-through capability. The medium-speed brushless DFIG in combination with a simplified two-stage gearbox promises a low-cost low-maintenance and reliable drivetrain for wind turbine applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…The harmonic components observed in PW current spectrum due to speed ripple are 38.7, 61.3, 83.9 and 95.5 Hz also can be obtained from (5). In addition of the harmonics induced in PW current, speed ripples have created considerable harmonic content in the torque spectrum with the frequencies obtained from:…”
Section: Speed Variationmentioning
confidence: 92%
See 1 more Smart Citation
“…The harmonic components observed in PW current spectrum due to speed ripple are 38.7, 61.3, 83.9 and 95.5 Hz also can be obtained from (5). In addition of the harmonics induced in PW current, speed ripples have created considerable harmonic content in the torque spectrum with the frequencies obtained from:…”
Section: Speed Variationmentioning
confidence: 92%
“…To date, a number of large BDFMs have been made, for example in Brazil with a 75 kW machine [3], China with the design of a 200 kW machine [4] and the 250 kW BDFM reported by the authors in [5] and shown in Figure 2 on test bed. The latter was built in a frame size D400 as a steppingstone towards a megawatt scale BDFM wind turbine.…”
Section: Introductionmentioning
confidence: 99%
“…The BDFM essentially behaves as a classical synchronous machine if the control winding is connected to a DC source, operating at so called natural synchronous speed under this condition. Note that the latter is half the synchronous speed of an equivalent DFIG having the same number of rotor poles which implies that a 2-stage, rather than a 3-stage, gearbox can be used for BDFG based wind turbines with immediately obvious reliability and economic benefits [9]. If a positive sequence frequency is applied to the control winding, i.e.…”
Section: A Background Theorymentioning
confidence: 99%
“…Another strong reliability advantage over the DFIM is the inherently medium-speed nature of the BDFG allowing the use of a simpler and more compact 2-stage gearbox as opposed to a high-speed 3-stage counterpart of DFIG wind turbines, which is less mechanically robust and prone to failures [9]. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The brushless doubly-fed machine is a variable speed electrical machine which shows particular promise in applications such as wind energy generation or as a VSD, but still needs design and thermal modelling verification [12]. The BDFM has two separate stator windings, which must be of different pole numbers to avoid direct coupling between them.…”
Section: Bdfm Machinementioning
confidence: 99%